Opening the air‐chamber of an oscillating water column spar buoy wave energy converter to avoid parametric resonance. Issue 14 (27th May 2021) - Davidson, Josh; Henriques, João C. C.; Gomes, Rui P. F.; Galeazzi, Roberto
Abstract: The oscillating‐water‐column (OWC) spar‐buoy is a type of wave energy converter that may exhibit undesirable large roll and pitch amplitudes caused by a dynamic instability induced by parametric resonance. The occurrence of this phenomenon not only reduces the power extraction but significantly increases the structural loads on the buoy, the turbine rotor and on the mooring system. The paper compares the parametric resonance behaviour of two configurations of an OWC spar‐buoy using experimental data obtained in a wave flume at a scale of 1:100. The configurations investigated were: (1) closed and (2) fully open‐air chamber. The experimental tests covered a wide range of regular and irregular waves, as well as in free decay experiments. Results showed that opening the air chamber reduces the coupling between the buoy and the OWC within, thus shifting the damped natural heave frequency of the system in comparison with the closed chamber configuration. This effect changes parametric resonance characteristics of the two configurations due to the coupling between roll/pitch and heave modes. Moreover, for specific wave frequencies, the occurrence of parametric resonance observed when the chamber is closed do not occur while the air chamber is fully open. These results suggest the possibility of controlling a pressure relief valve installed on top of the device to reduce parametric resonance whenever this dynamic instability is detected.